Identification of molecular signatures and pathways common to blood cells and brain tissue of amyotrophic lateral sclerosis patients. (2019) - Rahman, Md. Rezanur; Islam, Tania; Huq, Fazlul; Quinn, Julian M.W.; Moni, Mohammad Ali
Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive motor neuron disease that is characterized by the death of neurons controlling voluntary muscles. Early diagnosis of ALS is difficult and detection is limited in sensitivity and specificity as well as by cost. Therefore, detecting ALS from blood cell analysis could improve the early diagnosis and treatment of the disease. The present study aimed to identify blood cell transcripts that reflect brain expression levels of factors linked to ALS progression. We analyzed blood cell and brain transcriptomics gene expression datasets (RNA-seq and microarray) in blood and brain. We identified 13 differentially expressed genes (DEG; ALS versus controls) common to blood cells and brain (DNAH6, HLA-DMB, HLA-A, EHD2, CMKLR1, PROS1, GAPT, CCR1, THBS1, CDK2, RAB27A, ITGB3 and C1orf162) that were commonly dysregulated between ALS blood and brain tissues. These data revealed significant neurodegeneration-associated molecular pathways in the signaling systems. Integration of these different analyses revealed dysregulation of a number of transcription factors, namely SP1, MYC, TP3, CTCF and SRF. In addition, we identified microRNAs altered in ALS: miR-29c, miR-21, let-7a, miR-377, miR-103, miR-369-3p, miR-494, miR-204, miR-29a. Thus, we have identified possible new links between pathological processes in the brain and transcripts in blood cells in ALS subjects that may enable the use of blood samples to diagnose and monitor ALS onset and progression.